Priapism: Comorbid Factors and Treatment Outcomes in a Contemporary Series - Henry P. Gottsch; Richard E. Berger; Claire C. Yang (Advances in Urology)
Objective. The goal of this study is to describe comorbid characteristics in patients who have priapism, and their treatment outcomes. Methods. Chart review was undertaken on men who had a diagnosis of priapism from a tertiary medical center, from 2000–2010. Men with priapism due exclusively to the use of prescription erectile aids and medications were not included in the review. Results. We identified 79 patients with the priapism. The most common type of priapism was the low flow variant. High flow priapism was identified in 2 patients. The most common general comorbid condition associated with priapism was mental illness (including substance abuse), which was present in 56% of the patients. Neurogenic priapism accounted for 19% of the total priapism events. Psychopharmaceutical agents and recreational drugs were commonly associated with ischemic priapism. Acute complications of priapism treatment were not common, but long-term complications, especially erectile dysfunction, were frequent. Conclusions. We describe the characteristics and outcomes of a large group of patients with priapism. Our experience at a tertiary care center indicates that mental illness, including substance abuse disorders, is a highly prevalent comorbid condition in men who experience priapism. Consistent with previous reports, erectile dysfunction is the most common complication from priapism and its treatment, occurring in the majority of men.